2000
DOI: 10.1128/aem.66.3.1120-1125.2000
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Chain Fatty Acids Affect Citrinin Production in the Filamentous Fungus Monascus ruber

Abstract: During submerged culture in the presence of glucose and glutamate, the filamentous fungus Monascus ruber produces water-soluble red pigments together with citrinin, a mycotoxin with nephrotoxic and hepatoxic effects on animals. Analysis of the 13 C-pigment molecules from mycelia cultivated with [1-13 C]-, [2-13 C]-, or [1,2-13 C]acetate by 13 C nuclear magnetic resonance indicated that the biosynthesis of the red pigments used both the polyketide pathway, to generate the chromophore structure, and the fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 28 publications
9
75
0
1
Order By: Relevance
“…Sodium nitrate supports sporulation, limited growth and gives intermediate pigment yields; the use of ammonium chloride results in repression of conidiation and the sexual cycle and leads to the best pigment yields [21,91]. In this medium, the dramatic pH decrease impairs pigment-amine interactions giving origin to red pigments according to Carels et al [92] and they also reported that nitrogen source determines pH evolution. In addition to ammonium chloride, peptone also yields superior growth and pigment production when compared with sodium nitrate [27,28,92].…”
Section: Effect Of Carbon Sourcementioning
confidence: 97%
“…Sodium nitrate supports sporulation, limited growth and gives intermediate pigment yields; the use of ammonium chloride results in repression of conidiation and the sexual cycle and leads to the best pigment yields [21,91]. In this medium, the dramatic pH decrease impairs pigment-amine interactions giving origin to red pigments according to Carels et al [92] and they also reported that nitrogen source determines pH evolution. In addition to ammonium chloride, peptone also yields superior growth and pigment production when compared with sodium nitrate [27,28,92].…”
Section: Effect Of Carbon Sourcementioning
confidence: 97%
“…Monascus pigments are used as food colorants and flavouring agents (Hajjaj et al, 2003). Monascus is able to produce strong red pigment including some useful primary metabolites such as ethyl alcohol, acids, esters, and other flavouring compounds and secondary metabolites i.e.…”
Section: Introductionmentioning
confidence: 99%
“…But the concentration of citrinin, a mycotoxin causing hepatonephrotoxic effects, needs to be controlled during angkak production by genetic mutation of the fungal strain, by adding nutrients like fatty acids to the fermentation medium (Hajjaj et al 2000), or by replacing rice with other solid substrate like dioscorea (Lee et al 2006a) which might change the citrinin concentration in angkak.…”
Section: Discussionmentioning
confidence: 99%